RESOLVING ORTHOCLASE DISSOLUTION PROCESSES WITH ATOMIC FORCE MICROSCOPY AND X-RAY REFLECTIVITY - Teng H.H.; Fenter P.; Cheng L.; Sturchio N.C. (My University, 2001)
Direct measuremens of orthoclase (001) were performed using in situ atomic force microscopy (AFM) and synchrotron X-ray reflectivity to reveal the Α-scale dissolution process as a function of pH and temperature. Distinct processes were observed, involving mainly terrace roughening at pH = 1.1 and step motion at pH = 12.9. A gel-like surface coating was observed to form at acidic pH under slow fluid flow-rate conditions. No coating was observed either at alkaline pH or at acidic pH under high fluid flow-rate conditions. The corresponding dissolution rates were measured directly at pH = 1.1 and 12.9 at ~50°C using real-time X-ray reflectivity measurements, and reacted interface structures were derived from crystal truncation rod measurements after reaction at both acidic and alkaline pH. Our observations reveal, under these experimental conditions, that 1) orthoclase dissolution is controlled by at least two separate surface reactions having distinct reactive sites; 2) dissolution is stoichiometric at alkaline pH and only minimally nonstoichiometric (limited to one unit-cell depth) at acidic pH; previously identified nonstoichiometric layer thicknesses derived from macroscopic measurements are associated with the formation of the gel-like coatings; 3) dissolution rates measured at freshly cleaved (001) surfaces are comparable to those derived from steady-state powder dissolution rates for both alkaline and acidic pH; and 4) elevated transient dissolution rates are not observed for freshly cleaved surfaces but are obtained under alkaline conditions after reacting the orthoclase (001) surface at acidic pH. These observations clarify differences in orthoclase dissolution mechanisms as a function of pH, demonstrate the utility of AFM and X-ray scattering methods for measuring Α-scale structures and face-specific dissolution rates on single crystals and place new constraints on the understanding of alkali feldspar weathering processes.